ACCOUNTING CONSERVATISM AND EARNINGS MANAGEMENT–INDONESIAN EVIDENCE - KRISMIAJI KRISMIAJI; RATNA PUJI ASTUTI (Jurnal Bisnis dan Akuntansi, 2020)
This study empirically examines the effects of accounting conservatism on earnings management. Earnings management is proxied by accrual earnings management (AEM) and measured by discretionary accruals. Accounting conservatism is measured by accrual conservatism. This study uses data from 108 companies listed on the Indonesia Stock Exchange from 2016 to 2018. By using the Multiple Regression Model that places earnings management as the dependent variable and accounting conservatism as an independent variable, this study proves that accounting conservatism has a positive effect on earnings management. Moreover, the business cycle (cycle), asset turnover (ROA), and sales growth (SG) are control variables that also control this research model.